The Trinajsto prase Ensemble and the Folk Music Revival in Slovenia - Drago Kunej (Muzikološki Zbornik)
The paper presents the Trinajsto prase ensemble and its formative role in the Slovenian folk music revival movement of the late twentieth century. It examines the ensemble’s repertoire, performance aesthetics, participatory ethos, direct engagement with folk music practices, and diverse influences, as well as its legacy among Slovenian revival musicians.